Rapid one-pot radiosynthesis of [carbonyl-11C]formamides from primary amines and [11C]CO2 - Federico Luzi; Antony D. Gee; Salvatore Bongarzone (SpringerOpen, 2020)
Abstract Background Formamides are common motifs of biologically-active compounds (e.g. formylated peptides) and are frequently employed as intermediates to yield a number of other functional groups. A rapid, simple and reliable route to [carbonyl-11C]formamides would enable access to this important class of compounds as in vivo PET imaging agents. Results A novel radiolabelling strategy for the synthesis of carbon-11 radiolabelled formamides ([11C]formamides) is presented. The reaction proceeded with the conversion of a primary amine to the corresponding [11C]isocyanate using cyclotron-produced [11C]CO2, a phosphazene base (2-tert-butylimino-2-diethylamino-1,3-dimethylperhydro-1,3,2-diazaphosphorine, BEMP) and phosphoryl chloride (POCl3). The [11C]isocyanate was subsequently reduced to [11C]formamide using sodium borohydride (NaBH4). [11C]Benzyl formamide was obtained with a radiochemical yield (RCY) of 80% in 15 min from end of cyclotron target bombardment and with an activity yield of 12%. This novel method was applied to the radiolabeling of aromatic and aliphatic formamides and the chemotactic amino acid [11C]formyl methionine (RCY = 48%). Conclusions This study demonstrates the feasibility of 11C-formylation of primary amines with the primary synthon [11C]CO2. The reactivity is proportional to the nucleophilicity of the precursor amine. This novel method can be used for the production of biomolecules containing a radiolabelled formyl group.